Pengaruh Struktur Modal, Kebijakan Dividen dan INVESTMENT OPPORTUNITY SET TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN KONSTRUKSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Irmayani, Irmayani; Mas’ud, Masdar; Djamereng, Asdar (Innovative: Journal Of Social Science Research, 2024)
Abstract This research aims to determine the effect of Capital Structure, Dividend Policy and Investment Opportunity Set (IOS) on Company Value in Construction Companies Listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 Period. The Independent Variables used in this study are the Capital Structure Ratio, Dividend Policy and Investment Opportunity Set (IOS). While the dependent variable is Company Value. The sample in this study is a Construction Company listed on the Indonesia Stock Exchange (IDX) which was selected based on certain criteria using the Purposive Sampling Method. The research method used in this study is multiple linear regression analysis and t-test processed with SPSS with data sources, namely secondary data in the form of annual reports of Construction Companies obtained from the Indonesia Stock Exchange. The results of this study indicate that: 1. Capital structure proxied by Debt to Equity Ratio and Investment Opportunity Set (IOS) proxied by Earning Per Share have a positive and significant effect on company value as measured by Price Book Value (PBV) 2. Capital structure proxied by Debt to Asset Ratio has a negative and significant effect on company value as measured by Price Book Value (PBV) 3. Capital structure proxied by Long Term Debt to Equity Ratio and Investment Opportunity Set (IOS) proxied by Market to Book Value of Asset Ratio and Capital Expenditures to Book Value of Assets have a negative and insignificant effect on company value as measured by Price Book Value (PBV) 4. Dividend policy proxied by Dividend Yield and Dividend Payout Ratio and Investment Opportunity Set (IOS) proxied by Capital Expenditures to Market Value of Asset. Has a positive and insignificant effect on the company's value as measured by Price Book Value (PBV) Keywords: Capital Structure, Dividend Policy, Investment Opportunity Set, Company Value, Indonesia Stock Exchange